Model Investasi Alternatif: Sebuah Studi Komparatif Antara Konvensional dan Islam - Ayief Fathurrahman (Unisia, 2012)
This article aims to discuss the comparison of the investment model in the perspective of conventional and islamic. By definition, there is no fundamental difference between investing in islamic economics and conventiona one, the definition is an investment in a particular sector, for profit. But fundamentally, they differ on the basis of philosophy and certain rules that govern it, so the procedure of investing according to islamic economics also largely be different from the procedures in conventional economics.Keywords : investment, islamic economics, conventional.